Cross‐cultural acceptance of a traditional yoghurt‐like product made from fermented cereal. (7th October 2014) - Akissoé, Noël H; Sacca, Carole; Declemy, Anne‐Laure; Bechoff, Aurelie; Anihouvi, Victor B; Dalodé, Générose; Pallet, Dominique; Fliedel, Géneviève; Mestres, Christian; Hounhouigan, Joseph D; Tomlins, Keith I
Abstract BACKGROUND Akpan is a traditional ready‐to‐drink fermented yoghurt‐like cereal beverage consumed in urban and rural areas in Benin. With the aim of adapting the product to new local and export markets, this work maps African and European consumer preferences for different types of Akpan. RESULTS A sensory profile of Akpan was created and consumer tests were conducted with 103 consumers of African origin and 74 consumers of European origin. Consumer acceptance was significantly correlated with fermented odour (r = −0.94) and milky taste (r = 0.92–0.97) attributes. Cluster analysis revealed different behaviour by African and European consumers with respect to acceptability of Akpan; European consumers did not like the sour taste and African consumers liked an intense sweet milky taste. CONCLUSION This study provides information on how Akpan, and other fermented yoghurt‐type cereal products, could be adapted to African and European consumer preferences. © 2014 Society of Chemical Industry